2004
DOI: 10.1016/s0002-9440(10)63127-6
|View full text |Cite
|
Sign up to set email alerts
|

Transgene Expression of α(1,2)-Fucosyltransferase-I (FUT1) in Tumor Cells Selectively Inhibits Sialyl-Lewis x Expression and Binding to E-Selectin without Affecting Synthesis of Sialyl-Lewis a or Binding to P-Selectin

Abstract: During inflammation, E- and P-selectins appear on activated endothelial cells to interact with leukocytes through sialyl-Lewis x and sialyl-Lewis a antigens (sLe(x/a)). These selectins can also interact with tumor cells in a sialyl-Lewis-dependent manner and for this reason, they are thought to play a key role in metastasis. Diverting the biosynthesis of sialyl-Lewis antigens toward nonadhesive structures is an attractive gene therapy for preventing the hematogenous metastatic spread of cancers. We have previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 41 publications
2
49
0
Order By: Relevance
“…While performing those experiments we had found that the hepatocarcinoma cells (HCC) HepG2, do not bind to P-selectin but interact with E-selectin exclusively through sLex glycoantigens. 11 We also found that HCC interact with L-selectin in a sulfate-dependent manner, but this interaction is not modified by FUT1 transduction. Thus, HepG2 cells represent a good model to study the role played solely by the inducible endothelial Eselectin and its tumoral partner sLex in the development of hepatocarinomas.…”
mentioning
confidence: 59%
See 2 more Smart Citations
“…While performing those experiments we had found that the hepatocarcinoma cells (HCC) HepG2, do not bind to P-selectin but interact with E-selectin exclusively through sLex glycoantigens. 11 We also found that HCC interact with L-selectin in a sulfate-dependent manner, but this interaction is not modified by FUT1 transduction. Thus, HepG2 cells represent a good model to study the role played solely by the inducible endothelial Eselectin and its tumoral partner sLex in the development of hepatocarinomas.…”
mentioning
confidence: 59%
“…The E-selectin-IgM chimera was produced by transiently transfecting the human 293-T cells as described. 11 …”
Section: Cell Lines Dnas and Lentiviral Transductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This characteristic substrate usage resulted in total elimination of sialyl Lewis x/a from both glycolipids and glycoproteins. Previously, two research groups introduced FUT1, which catalyzes the addition of a terminal fucose in a1,2 linkage to a lactosamine residue, into HT29 cancer cells and succeeded in reducing the level of sialyl Lewis x (32,33). However, their results with sialyl Lewis a were inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…However, their results with sialyl Lewis a were inconsistent. The discrepancy between these two studies seems to be derived from the heterogeneity of expression patterns of carbohydrates that can occur in a cancer cell line (33). This again indicates the difficulty in applying gene delivery of FUT1 for the treatment of cancer cells in the human gastrointestinal tract, which displays immense heterogeneity and variation.…”
Section: Discussionmentioning
confidence: 99%